Twelve Months Post-treatment Results From the Norwegian Version of Improving Access to Psychological Therapies - Sæther, Solbjørg Makalani Myrtveit; Knapstad, Marit; Grey, Nick; Smith, Otto R. F. (Frontiers in Psychology, 2019)
Objectives: Prompt Mental Health Care (PMHC) is the Norwegian version of the England’s Improving Access to Psychological Therapies (IAPT). Both programs have been associated with substantial symptom reductions from pre- to post-treatment. The present study extends these findings by investigating symptom levels at 12-months post-treatment, as well as treatment outcome in relation to low- vs high-intensity treatment forms. Design and outcome measures: A prospective cohort design was used. All participants (n=1530) were asked to complete the Patient Health Questionnaire-9 (PHQ-9) and the Generalized Anxiety Disorder-7 questionnaire (GAD-7) at baseline and up to 12-months post-treatment. Cohen’s d was used as effect size measure. Sensitivity analyses were conducted to examine the impact of the high missing data rates at post-treatment (≈44%) and 12-months post-treatment (≈58%). Results: A large symptom reduction was seen from baseline to 12-months post-treatment for both PHQ (d=-.98) and GAD (d=-.94). Improvements observed at post-treatment were largely maintained at 12-months post-treatment (PHQ (d=.10) and GAD (d=.09). Recovery rates decreased only slightly from 49.5% at post-treatment to 45.0% at follow-up. Both low- and high-intensity treatment forms were associated with substantial and lasting symptoms reductions (-1.26≤d≤-.73). Sensitivity analyses did not substantially alter the main results. Conclusions: The findings suggest long-lasting effects of the PMHC program and encourage the use of low-intensity treatment forms in PMHC like settings.